Benign paroxysmal positional vertigo in outpatient practice: Diagnosis and treatment - N. V. Bestuzheva; V. A. Parfenov; L. M. Antonenko (Неврология, нейропсихиатрия, психосоматика)
Dizziness is one of the common reasons for visits to physicians of various specialties; the data of foreign investigations show that benign paroxysmal positional vertigo (BPPV) is most frequently encountered.Objective: to study the causes of dizziness, to analyze the frequency of BPPV and the efficiency of its treatment in outpatient practice.Patients and methods. The investigation enrolled 80 patients, including 55 (68.7%) women and 25 (31.3%) men, aged 18 to 75 years (mean age 53.8±12.8 years), who complained of dizziness and sought for medical advice in the Therapeutic-and-Diagnostic Unit, A.Ya. Kozhevnikov Clinic of Nervous System Diseases, I.M. Sechenov First Moscow State Medical University.Results. The most common causes of dizziness in outpatient practice were BPPV (46.2%) and postural phobic vertigo (35%). The diagnosis of VPPV, if special positional testing (Dix-Hallpike and McClure-Pagnini tests) was carried out, was shown to create no significant difficulties. The diagnosis was not established in the majority (97.5%) of the patients; effective treatment was performed in one of the patients. Combined treatment, by performing the positional tests and using betaserc for 2 months, led to complete resolution of positional vertigo in most (97.3%) patients.Discussion. The findings indicate the efficiency of examining patients with complaints of dizziness, by using the special otoneurological tests to detect BPPV. The purposeful questioning of patients with BPPV can suspect this disease in the majority of cases. Our investigation shows the high efficiency of rehabilitation maneuvers for BPPV, which agrees well with the data of other authors. Physicians’ poor awareness of BPPV among physicians and the high efficiency of its treatment in outpatient practice are noted.